Reingeniería de procesos de la cooperativa de ahorro y crédito Mushuc Runa Ltda. de la ciudad de Ambato - Choco Pandashina, Juan José (2015)
The main objective of this work was raised analyze the methodology of reengineering processes to improve the services offered MushucRuna Cooperative in the city of Ambato , allowing partners to provide quality service : efficient and effective . To obtain information inductive, deductive, analytical, synthetic and descriptive methods were used, and data collection met the Manager, a survey was applied to the 98 employees of the entity and 399 partners, in order to learn from the external perspective the strengths and weaknesses of the service. In the first instance the key processes of the Cooperative were identified later with the information gathered was found that there flaws in the process of lending and collection development bonus, the same to be redesigned; because they affect care - customer satisfaction. The reengineering process is expected to MushucRuna Cooperative offers less time on operations and better use of resources which will result in benefits for both the company and its partners. The research work includes: The title of the general subject of research. Summary that compliance with the overall objective is exposed, the methodology and the main results. Introduction, problematic because of the investigation that led to the achievement of the specific objectives is contextualized. With Literature Review; concepts and theories that support the field work are presented, which is subdivided into the referential and conceptual framework. Materials, methods and techniques used in the study and determination of the population with its respective sample. The results yield information obtained from interviews and surveys. Discussion that contains the key used to reengineer processes, and the approach of new procedures designed to improve the management performed. Conclusions, referring to the main results obtained after research and recommendations given to managers, proposal to improve the detected problems. Bibliography includes books, journals and magazines that support the theory advanced at work. Finally mentioned Annexes, it has approved the project summary formats and research techniques used in the study